COGNITIVE DEVELOPMENT AND ITS ROLE IN EFFECTIVE PEDAGOGY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Cognitive development forms the psychological foundation of human learning and educational practice. Understanding how learners think, reason, and construct knowledge is essential for designing effective pedagogy. This paper explores major theories of cognitive development, including those of Piaget, Vygotsky, and Bruner, and examines how cognitive psychology shapes modern instructional strategies. It highlights the relationship between cognition and pedagogy, discusses developmental stages, and evaluates practical classroom applications. Ultimately, it argues that integrating cognitive theory into pedagogy promotes not only intellectual growth but also independent, reflective, and creative learners.